Development of Inapparent Dengue Associated With Increased Antibody Levels to Aedes aegypti Salivary Proteins: A Longitudinal Dengue Cohort in Cambodia . (27th October 2021) - Manning, Jessica E; Chea, Sophana; Parker, Daniel M; Bohl, Jennifer A; Lay, Sreyngim; Mateja, Allyson; Man, Somnang; Nhek, Sreynik; Ponce, Aiyana; Sreng, Sokunthea; Kong, Dara; Kimsan, Soun; et al.
Abstract: Background: We established the first prospective cohort to understand how infection with dengue virus is influenced by vector-specific determinants such as humoral immunity to Aedes aegypti salivary proteins. Methods: Children aged 2–9 years were enrolled in the PAGODAS (Pediatric Assessment Group of Dengue and Aedes Saliva) cohort with informed consent by their guardians. Children were followed semi-annually for antibodies to dengue and to proteins in Ae . aegypti salivary gland homogenate using enzyme-linked immunosorbent assays and dengue-specific neutralization titers. Children presented with fever at any time for dengue testing. Results: From 13 July to 30 August 2018, we enrolled 771 children. At baseline, 22% (173/770) had evidence of neutralizing antibodies to 1 or more dengue serotypes. By April 2020, 51 children had symptomatic dengue while 148 dengue-naive children had inapparent dengue defined by neutralization assays. In a multivariate model, individuals with higher antibodies to Ae . aegypti salivary proteins were 1.5 times more likely to have dengue infection (hazard ratio [HR], 1.47 [95% confidence interval CI, 1.05–2.06]; P = .02), particularly individuals with inapparent dengue (HR, 1.64 [95% CI, 1.12–2.41]; P = .01). Conclusions: High levels of seropositivity to Ae. aegypti salivary proteins are associated with future development of dengue infection, primarily inapparent, in dengue-naive Cambodian children. Clinical Trials Registration: NCT03534245 Abstract : Results from a longitudinal pediatric cohort in Cambodia demonstrated that children with high levels of antibodies to Aedes aegypti mosquito saliva were more likely to get dengue, but were also less likely to have clinical symptoms.